Nine Additional Cultivated Species of Asteraceae from Java - Irsyam, Arifin Surya Dwipa; Irwanto, Rina Ratnasih (UIN Sunan Gunung Djati Bandung, 2019)
Asteraceae is one of the largest families in the Angiosperm. It comprises of 24,000‒30,000 species which are grouped into 1,600‒1,700 genera and distributed in a cosmopolitan range. Based on Backer and Bakhuizen van den Brink’s 1965 works, they identified 227 species of Asteraceae in Java. Many of them are introduced species, both cultivated or naturalized. However, the cultivated species have not been recorded. The aim of this study is to provide information about new records of cultivated Asteraceae in Java. The observations were carried out in Bandung, Bogor, and Sumedang, during January to February 2019. Nine additional species were discovered; species belonging to genera Caputia (two species), Curio (two species), Kleinia (one species), Gymnanthemum (one species), Senecio (two species), and Tarlmounia (one species). These species were grouped into two tribes: Vernonieae and Senecioneae. This study indicates that information on Asteraceae of Java need to be updated.